Temperature‐body size responses in insects: a case study of British Odonata. (26th February 2020) - Wonglersak, Rungtip; Fenberg, Phillip B.; Langdon, Peter G.; Brooks, Stephen J.; Price, Benjamin W.
Abstract : 1. Body size is highly correlated with physiological traits, fitness, and trophic interactions. These traits are subject to change if there are widespread reductions of body size with warming temperatures, which is suggested as one of the 'universal' ecological responses to climate change. However, general patterns of body size response to temperature in insects have not yet emerged. 2. To address this knowledge gap, we paired the wing length (as a proxy for body size) of 5331 museum specimens of 14 species of British Odonata with historical temperature data. Three sets of analyses were performed: (i) a regression analysis to test for a relationship between wing length and mean seasonal temperature within species and subsequent comparisons across species and suborders; (ii) an investigation of whether the body size of species has an effect on sensitivity to warming temperature; and (iii) a linear‐mixed effects model to investigate factors that potentially affect temperature–size response. 3. The regression analysis indicated that wing length is negatively correlated with mean seasonal temperatures for Zygoptera, whereas Anisoptera showed no significant correlation with temperature. 4. There is a significant decline in wing length of all Zygoptera (but not Anisoptera) with collection date, suggesting that individuals emerging later in the season are smaller. 5. Life‐cycle type was not important for predicting wing length–temperature responses, whereas sex, species, and suborder were indicated as important factors affecting the magnitude of temperature–size responses in Odonata. 6. Overall, wing lengths of Zygoptera are more sensitive to temperature and collection date than Anisoptera. Abstract : Mean seasonal temperature was negatively correlated with body size of Zygoptera, whereas Anisoptera showed no significant correlation with temperature. Grouped by sub‐order, wing length in Zygoptera decreases by an average of 1.10 mm per °C, whereas wing length of Anisoptera, as a whole, does not significantly change with temperature. A significant decline in wing length of all Zygoptera (but not Anisoptera) with advancing collection date was found, suggesting that individuals emerging later in the season are smaller.